2012
DOI: 10.3803/enm.2012.27.4.276
|View full text |Cite
|
Sign up to set email alerts
|

APOA5Polymorphism Is Associated with Metabolic Syndrome in Korean Postmenopausal Women

Abstract: Background:Menopause is an independent risk factor in metabolic syndrome which induced an alteration of the lipid metabolism by hormonal changes. Apolipoprotein A5 gene (APOA5) was related to the regulation of triglyceride and high density lipoprotein cholesterol (HDL-C) level with biosynthesis and decomposition. This study was conducted to investigate the relationship between APOA5 polymorphism and metabolic syndrome in Korean postmenopausal women. Methods: This study included 307 postmenopausal women with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Most studies were from Asia ( n = 17) [ 11 , 15 , 22 , 24 , 26 , 29 – 32 , 34 – 36 , 48 , 49 , 52 , 55 , 57 ] and Europe ( n = 8) [ 27 , 33 , 46 , 47 , 50 , 51 , 54 , 56 ], while we found just one study that was conducted in the USA [ 53 ], and four studies that were from Africa [ 19 , 21 , 25 , 28 ]. The age range of the participants was 18 to 79, and the majority of studies were performed among both sexes, while three studies included only women [ 31 , 32 , 51 ]. Twenty-two studies were consistent with Hardy-Weinberg equilibrium (HWE) [ 11 , 21 , 22 , 24 , 25 , 27 , 29 , 30 , 32 35 , 46 , 48 51 , 53 – 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies were from Asia ( n = 17) [ 11 , 15 , 22 , 24 , 26 , 29 – 32 , 34 – 36 , 48 , 49 , 52 , 55 , 57 ] and Europe ( n = 8) [ 27 , 33 , 46 , 47 , 50 , 51 , 54 , 56 ], while we found just one study that was conducted in the USA [ 53 ], and four studies that were from Africa [ 19 , 21 , 25 , 28 ]. The age range of the participants was 18 to 79, and the majority of studies were performed among both sexes, while three studies included only women [ 31 , 32 , 51 ]. Twenty-two studies were consistent with Hardy-Weinberg equilibrium (HWE) [ 11 , 21 , 22 , 24 , 25 , 27 , 29 , 30 , 32 35 , 46 , 48 51 , 53 – 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two studies were consistent with Hardy-Weinberg equilibrium (HWE) [ 11 , 21 , 22 , 24 , 25 , 27 , 29 , 30 , 32 35 , 46 , 48 51 , 53 – 57 ]. However, in three studies, HWE was not in equilibrium [ 15 , 36 , 47 ], and in six studies, HWE was not reported [ 19 , 24 , 26 , 28 , 31 , 52 ]. Seventeen studies used NCEP ATP III criteria [ 11 , 22 , 27 , 28 , 31 – 34 , 46 , 47 , 49 – 54 , 56 ], ten studies used IDF criteria [ 15 , 19 , 21 , 24 , 25 , 29 , 30 , 35 , 36 , 48 ], and three studies used modified definition for identifying MetS [ 26 , 55 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This discordance across studies may be related to the differences among ethnic groups. The C allele of the APOA5 -1131 T > C is more common among Asian populations (34% frequency in Japanese, 28-30% in Koreans, and 7.4% in Caucasians) [ 26 , 27 ]. The living conditions and progression of the disease as well as other subject characteristics may also affect the results.…”
Section: Discussionmentioning
confidence: 99%